Usefulness of virtual chromoendoscopy in the evaluation of subtle small bowel ulcerative lesions by endoscopists with no experience in videocapsule - Rimbaş, Mihai; Zahiu, Denise Carmen Mihaela; Voiosu, Andrei Mihai; Voiosu, Theodor Alexandru; Zlate, Alina Ana-Maria; Dinu, Roxana; Galasso, Domenico; Minelli Grazioli, Leonardo; Campanale, Mariachiara; Barbaro, Federico; Mateescu, Bogdan Radu; Busuioc, Bogdan; Iordache, Tiberiu; Dolofan, Oana; Popescu, Adelina Maria; Balaban, Vasile Daniel; Raducan, Mircea Mihai; Spada, Cristiano; Băicuş, Cristian Răsvan; Costamagna, Guido (Endoscopy International Open, 2016)
Background and study aims: In videocapsule endoscopy examination (VCE), subtle variations in mucosal hue or pattern such as those seen in ulcerations can be difficult to detect, depending on the experience of the reader. Our aim was to test whether virtual chromoendoscopy (VC) techniques, designed to enhance the contrast between the lesion and the normal mucosa, could improve the characterization of ulcerative mucosal lesions. Patients and methods: Fifteen trainees or young gastroenterologists with no experience in VCE were randomly assigned to evaluate 250 true ulcerative and 100 false ulcerative, difficult-to-interpret small bowel lesions, initially as white light images (WLI) and then, in a second round, with the addition of one VC setting or again as WLI, labeling them as real lesions or artifacts.Results: On the overall image evaluation, an improvement in lesion characterization was observed by adding any chromoendoscopy setting, especially Blue mode and FICE 1, with increases in accuracy of 13 % [95 %CI 0.8, 25.3] and 7.1 % [95 %CI – 17.0, 31.3], respectively. However, when only false ulcerative images were considered, with the same presets (Blue mode and FICE 1), there was a loss in accuracy of 10.7 % [95 %CI – 10.9, 32.3] and 7.3 % [95 %CI – 1.3, 16.0], respectively. The interobserver agreement was poor for both readings.Conclusions: VC helps beginner VCE readers correctly categorize difficult-to-interpret small bowel mucosal ulcerative lesions. However, false lesions tend to be misinterpreted as true ulcerative with the same presets. Therefore care is advised in using VC especially under poor bowel preparation.